Implementing primary eye care in private practises in Malaysia: the challenges faced by optometrists - Yahaya, Nurul Ain; Musa, Azuwan; Che Azemin, Mohd Zulfaezal; A. Rahman, Nor Azlina (Malaysian Medical Association, 2023)
Objective: In Malaysia, optometrists' role in the private sector is limited compared to their counterparts elsewhere. Primary eye care (PEC) is still not widely offered in private practises despite its demand to reduce the public's eye morbidity. This study aims to explore the challenges perceived by the private sector optometrists in implementing PEC in Malaysia. Materials and Methods: In-depth interview using semistructured open-ended questions were designed to explore the challenges of implementing PEC. Fifteen private optometrists across Malaysian were interviewed via purposive sampling until the data were saturated. The interviews were audio-recorded, transcribed and analysed. Results: Four major themes emerged: working environment, support and recognition, self-sufficiency and customer influence. The first major theme identified a lack of time and equipment in the workplace as a barrier to PEC implementation. The second major theme acknowledges the lack of support and recognition for PEC practise from financial bodies, the government, Malaysian Optical Council (MOC) and other eye professionals. Meanwhile, some practising optometrists faced significant challenges due to their lack of self-sufficiency regarding skills, knowledge and confidence. The final major theme, customer influence, reflects the customer's role in shaping eye care delivery through their perception and acceptance of PEC. Conclusion: Each of the issues identified played a significant impact in impeding PEC implementation in Malaysia. This study is the first step toward developing tailored interventions to improve eye care delivery in Malaysia